Can alteration experiments on impact melts from El'gygytgyn and volcanic glasses shed new light on the formation of the Martian surface?. (25th June 2013) - Hellevang, Helge; Dypvik, Henning; Kalleson, Elin; Pittarello, Lidia; Koeberl, Christian
Abstract: This investigation involved three specimens: an altered felsic sample of impactite from the ICDP El'gygytgyn drill core D1c, and two reference volcanics from Iceland, namely a rhyolitic glass and a basaltic glass. The goal of this work was to better understand the alteration of impact melt and volcanic glass, and to apply the results to an investigation of alteration processes below the surface of Mars. Hydrothermal batch alteration experiments with the El'gygytgyn sample showed formation of various silica phases such as cristobalite, opal, and quartz. According to geochemical modeling, zeolites were also expected, but zeolite minerals already present in the impactite prior to the experiment may have masked possible experimental zeolite growth. Basaltic glass was altered to smectite, talc, and opal. The accompanying numerical modeling gave results that were similar or comparable to the laboratory experiments. Rhyolitic glass was kinetically more stable than basaltic glass, and showed only minor formation of calcite and feldspar during the 3‐week experiment. The study showed that closed‐system isochemical alteration of both siliceous and mafic glasses and melts results in the formation of smectites and zeolites. Therefore, to link alteration features on Mars to specific physical conditions, the exact identity of the mineral phases present in surface rocks must be known. Moreover, our simulations on closed‐system isochemical alteration showed that the fraction of zeolites and silica formed relative to smectite depends on the source mineral altered. Therefore, fractions of these mineral groups present in the Martian soil may be used to better predict source rock characteristics.